Depth‐Partitioning of Particulate Organic Carbon Composition in the Rising and Falling Stages of the Amazon River - Sarah Z. Rosengard; Jose Mauro S. Moura; Robert G. M. Spencer; Carl Johnson; Ann McNichol; Andrew D. Steen; Valier Galy (Geochemistry, Geophysics, Geosystems, 2024)
Abstract The Amazon River mobilizes organic carbon across one of the world's largest terrestrial carbon reservoirs. Quantifying the sources of particulate organic carbon (POC) to this flux is typically challenging in large systems such as the Amazon River due to hydrodynamic sorting of sediments. Here, we analyze the composition of POC collected from multiple total suspended sediment (TSS) profiles in the mainstem at Óbidos, and surface samples from the Madeira, Solimões and Tapajós Rivers. As hypothesized, TSS and POC concentrations in the mainstem increased with depth and fit well to Rouse models for sediment sorting by grain size. Coupling these profiles with Acoustic Doppler Current Profiler discharge data, we estimate a large decrease in POC flux (from 540 to 370 kg per second) between the rising and falling stages of the Amazon River mainstem. The C/N ratio and stable and radiocarbon signatures of bulk POC are less variable within the cross‐section at Óbidos and suggest that riverine POC in the Amazon River is predominantly soil‐derived. However, smaller shifts in these compositional metrics with depth, including leaf wax n‐alkanes and fatty acids, are consistent with the perspective that deeper and larger particles carry fresher, less degraded organic matter sources (i.e., vegetation debris) through the mainstem. Overall, our cross‐sectional surveys at Óbidos highlight the importance of depth‐specific sampling for estimating riverine export fluxes. At the same time, they imply that this approach to sampling is perhaps less essential with respect to characterizing the composition of POC sources exported by the river.